Characterization Of β-TCP Coated On Stainless Steel 316 - Ariff, Ummi Fatisya Ain (Universiti Sains Malaysia, 2022)
Biomaterials are materials designed to interact with the human body. Stainless steels, particularly 316 types, are the most often used metallic biomaterials for biomedical applications due to their superior biocompatibility, low cost, availability and high strength. However, leaching of metallic ions into surrounding tissues is a huge disadvantage which can cause renal and cardiac problems. By coating ß-TCP onto the surface of 316 SS is an alternate way for preventing iron ions from spreading and destroying human tissues. In this project, the main objective are to coat beta tricalcium phosphate on 316 SS via spray coating technique and to evaluate the effect of number of coatings on the properties of the coated 316 SS. The parameter used is different number of coatings which is 1 to 5 layers. The slurry was prepared by mixing PVA into distilled water. After that, let it cool to room temperature and the add β-TCP powder with the right composition. Then, the slurry is sprayed on the 316 SS substrate with different number of layers and sintered at 700°C. Characterization involved are Scanning Electron Microscope (SEM), Atomic Force Microscopy (AFM), Vickers Microhardness Test and Bioactivity test in HBSS. From the result obtained, the coating with five layers had the greatest thickness and hardness while for the surface roughness coating with three layers had the highest value of 6.131 nm. Lastly, for bioactivity test sample with coating of three layer has less gained in weight, while sample with coating of five layer has great weight loss. The amount of weight loss was influenced significantly by the addition layer of coating, particularly at layer five. Increasing number of coatings, increased weight loss.